2019
DOI: 10.1159/000497377
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Physicians towards Different Types of Euthanasia in Kuwait

Abstract: Objective: Although in recent years the world has witnessed great advances in the medical field, much ambiguity still surrounds the issue of euthanasia and physician-assisted suicide, with increasingly favorable attitudes among physicians around the world. In our study, we aimed to assess the attitudes of physicians in Kuwait towards different types of euthanasia and examine whether physicians’ frequent encounters with terminally ill patients were associated with their approval. Subjects and Methods: We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
3
16
2
Order By: Relevance
“…12 PAS, on the other hand, is defined as the provision of prescription for lethal medication to a competent patient who is terminally ill upon his/her request to take on their own life. 14 Other terms used to describe PAS are 'medical aid/ assistance in dying', 'assisted dying', 'physician-assisted death' and 'suicidal euthanasia'. 16 Non-voluntary euthanasia refers to the termination of life without explicit request and is typically practiced on patients who lack decisional capacity.…”
Section: Physician-assisted Suicide and Euthanasiamentioning
confidence: 99%
“…12 PAS, on the other hand, is defined as the provision of prescription for lethal medication to a competent patient who is terminally ill upon his/her request to take on their own life. 14 Other terms used to describe PAS are 'medical aid/ assistance in dying', 'assisted dying', 'physician-assisted death' and 'suicidal euthanasia'. 16 Non-voluntary euthanasia refers to the termination of life without explicit request and is typically practiced on patients who lack decisional capacity.…”
Section: Physician-assisted Suicide and Euthanasiamentioning
confidence: 99%
“…It has been shown that country of origin, cultural background and religious background influence physicians' attitudes and practice of medicine, including EOL care, although only in relatively few studies [6,7]. Some previous studies have shown that Muslim physicians are more likely than non-Muslim physicians to object to the concepts of withdrawal from life support or artificial nutrition, physician-assisted suicide, and terminal sedation [6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…While I laud Abohaimed et al [1] for taking on the important, challenging, and seldom discussed topic of euthanasia, I am also constrained to point out some deficiencies (i) in definition and typing, (ii) in consistency of “types” of euthanasia (4 in text and 3 in figure), and (iii) in bundling together “types” that has different ethical and legal implications. Admittedly, most of the definitions of euthanasia are descriptive, and there are multiple interpretations in the literature.…”
mentioning
confidence: 99%
“…Passive and indirect “types” are not to be considered euthanasia, and my reasons are stated in comments that follow the authors statements. The authors state passive euthanasia is “withholding or withdrawing of life-sustaining treatment either at the request of the patient or when prolonging life is considered futile” [1]. Withholding or withdrawing of life-sustaining treatment at the request of a patient is not euthanasia as it is grounded on “patient autonomy,” one of the basic principles of medical ethics [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation